The Anthelmintic Activity of Ethanol 96% Extract of Papaya Stem (Carica papaya l.) from Indonesia - Bestari, Rochmadina Suci; Sutrisna, EM; Ibrahim, Muhammad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2020)
Introduction : Soil transmitted helminth (STH) infection incidence is still high in the world, become main problem in developing countries including Indonesia. Papaya’s stem was traditionally used as anthelmintic in Indonesia.Objective : This study aims to determine the anthelmintic effect of 96% ethanolic extract of papaya (Carica papaya L.) stem. Material and Method : This study used a laboratory experimental research design with posttest only with control group design approach. The samples were 90 Ascaris suum worms, divided into 6 groups, 3 times repeated. The first group was treated by Aquadest as negative control, the second group was treated by Pyrantel Pamoate as positive control in 0.5 concentration. The third, fourth, fifth and sixth groups were treated by 96% ethanolic extract of papaya (Carica papayaL.) stem in 0.2 b/v, 0.4 b/v, 0.6 b/v and 0.8 b/v concentration respectively. Data were collected by observation of total mortality time of Ascaris suum worm every 3 hours. The anthelmintic effects was analysis by Post hoc Mann-Whitney with significancy level at p<0.05.Result : There was significant difference between the 96% ethanolic extract of papaya (Carica papaya L.) stem (0.2 b/v, 0.4 b/v, 0.6 b/v and 0.8 b/v) with control negative with Pvalue < 0.05 by Mann Whitney Test.Conclusion : The 96% ethanolic extract of papaya (Carica papaya L.) stem have potential as anthelmintic.